FAKTOR-FAKTOR YANG MEMPENGARUHI PELAYANAN PRIMA TERHADAP KEPUASAAN PASIEN RAWAT JALAN DI UNIT HEMODIALISIS RS X PEKANBARU TAHUN 2025 - Anggy Vidian; Hetty Ismainar; Budi Hartono; Reno Renaldi; Doni Jepisah; Awaliyah Ulfah (Jurnal Keperawatan Abdurrab, 2026)
The concept of excellent service consists of six standards: Attitude, Attention, Action, Ability, Appearance, and Accountability. This study aims to analyze the factors influencing excellent service on outpatient satisfaction in the Hemodialysis Unit of X Hospital Pekanbaru in 2025 using a quantitative method and a cross-sectional approach. The sample included 138 respondents selected through total sampling. Multivariate analysis was conducted using a modified multiple logistic regression model for prediction and risk factors. The study found that the majority of respondents were satisfied (56.5%), and most rated staff attitude as positive (53.6%), attention (55.8%), good action (52.9%), good ability (60.1%), good appearance (62.3%), accountability (58.7%), and had been undergoing hemodialysis for ≤12 months (56.5%). The most dominant variable affecting patient satisfaction was attitude (P value = 0.001) without controlling for duration of HD, where negative attitude increased the risk of dissatisfaction by 4.073 times (CI 95%: POR = 1.745–9.506). After controlling for HD duration, attention (P = 0.006), action (P = 0.002), and ability (P = 0.002) were also significantly associated, with dissatisfaction risks of 3.003 (CI 95%: 1.364–6.606), 3.502 (CI 95%: 1.561–7.857), and 3.802 (CI 95%: 1.654–8.740), respectively. The Nagelkerke R Square value of 0.317 indicates that 31.7% of patient satisfaction is explained by these variables, while the remaining 68,3% is attributed to other unexamined factors. X Hospital needs to improve its services by taking a personal approach to employees who have negative attitudes, increasing collaboration, open communication among health workers, increasing periodic evaluations and direct supervision by superiors, implementing an internal patient triage system, increasing socialization of SOPs and pastient service flow, improving officer skills by training and conducting officer performance assessments.